UMNO-PAS Islamization Policy Under The Leadership of Abdullah Badawi and Najib Razak - Sabtu, Muhamad Helmy; Ismail, Amalin Sabiha; Mohamad Suhaimy, Khairul Azman (Journal of Social Transformation and Regional Development, 2021)
Political Islamization in Malaysia is represented by the two largest Malay-Muslim parties, UMNO and PAS. This article analyzes the Islamization policy introduced and implemented by UMNO and PAS during the era of Abdullah Badawi and Najib Razak as Prime Minister of Malaysia. This research presented four policies implemented by UMNO; Islam Hadhari, the Wasatiyyah principle, the Shariah Indeks of Malaysia, and the cooperation between UMNO and PAS. The four principles of Islamization introduced by PAS include; the agenda of the Islamic State, the implementation of Hudud, the Islam democratization, and the concept of Welfare State. The proposing of Islamization policies by both parties clearly shows that Islam has been one of the key indicators of country governance. The study also found that UMNO-PAS’s Islamization policy has finally pioneered the cooperation between two parties from 2015 until now.